Comparison of interpolations used in solving delay differential equations by runge-kutta method - Ismail, Fudziah; Al-Khasawneh, Raed Ali; Suleiman, Mohamed (2003)
Delay differential equations are solved using embedded Singly Diagonally Implicit Runge-Kutta (SDIRK) method (3,4) in (4,5). The approximation of the delay term is obtained by Newton divided difference interpolation and interpolation developed by In't Hout. Numerical results based on these two types of interpolation are compared. The stability polynomial and the stability regions of SDIRK method (2,2) using In't Hout interpolation for the delay term are presented.